Monitoring cattle farms using Cloud Computing-based Internet of Things (IOT) tools using Artificial Intelligence Methods - Rahayu, Ria Sri; Wahyu Wibowo, Ari Purno (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
Cows are animals valuable commodity and it one of the economic supports for people in animal husbandry and agriculture, cows it selves able to used for meat, there are currently many cattle farms in Indonesia and spread across several regions, the cattle breeding or livestock proses Currently including in two types, farming in cages and farming outside cages, the cows themselves can easily be infected by diseases which spread quickly to other cows, large numbers of cows diasble to monitor because of the limited equipment and number of farmers, the number of cages is flat being far from settlement areas will make the selection process difficult and disable simultaneously. To handle this problem, it can be deal with using sensor devices that are configured with IoT devices. These devices easily monitored health and room temperature which can be used for 24 hours, the results of the data from the temperature sensor are displayed information that represent like dashboard and displays the cow's temperature data in graphical view. The system sets a temperature range of 38.6 - 38.9. If above this temperature the cow is in distemper condition and needs to be quarantined and won’t spread to another cow. This system provide information and make it easier for farmers to supervise their livestock.